2010
DOI: 10.1007/s12263-010-0176-8
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in the selenoprotein S and 15-kDa selenoprotein genes are associated with altered susceptibility to colorectal cancer

Abstract: Selenium (Se), a dietary trace metal essential for human health, is incorporated into *25 selenoproteins including selenoprotein S (SelS) and the 15-kDa selenoprotein (Sep15) both of which have functions in the endoplasmic reticulum protein unfolding response. The aim of this study was to investigate whether genetic variants in such selenoprotein genes are associated with altered risk of colorectal cancer (CRC). A Korean population of 827 patients with CRC and 733 healthy controls was genotyped for 7 SNPs in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
77
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(79 citation statements)
references
References 29 publications
(39 reference statements)
1
77
0
1
Order By: Relevance
“…Indeed, minor allelic variants of SEP15 rs5845 have been shown to have functional consequences. These SNPs have been reported to affect breast cancer risk (Hu et al 2001) and the risk of lung cancer in smokers (Jablonska et al 2008) and also to influence the risk of rectal cancer in men (Sutherland et al 2010). It is important highlight that these studies cited also serve to illustrate the absence of neurobiological studies for SEP15 gene.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, minor allelic variants of SEP15 rs5845 have been shown to have functional consequences. These SNPs have been reported to affect breast cancer risk (Hu et al 2001) and the risk of lung cancer in smokers (Jablonska et al 2008) and also to influence the risk of rectal cancer in men (Sutherland et al 2010). It is important highlight that these studies cited also serve to illustrate the absence of neurobiological studies for SEP15 gene.…”
Section: Discussionmentioning
confidence: 99%
“…Related to this finding, polymorphisms in the SELS gene as well as the gene encoding another ER selenoprotein, SEP15, were recently correlated to increased risk for colorectal cancer (247). SELS has been shown to be a glucose-regulated protein involved in the retrotranslocation of misfolded proteins from the ER into the cytosol for proteasomal degradation (80,128).…”
Section: F Inflammation Linked To Er Stressmentioning
confidence: 97%
“…Genetic variants in the SelS gene were shown to regulate the circulating levels of proinflamatory cytokines including IL-6, IL-1␤, and TNF-␣ (72) and have been linked to the development of coronary heart disease, ischemic stroke (4), preeclampsia (261), gastric (315) and colorectal (337) cancer, and other conditions that are associated with increased inflammation. Moreover, characterization of the recently developed SelK knockout mouse model demonstrated that SelK deficiency leads to deficient Ca 2ϩ flux during immune cell activation and impaired immune response (358).…”
Section: Selenoproteins K and Smentioning
confidence: 99%